Mitochonic acid 5 increases boar sperm quality by mitigating mitochondrial dysfunction - Wang, Ruyuan; Adetunji, Adedeji O.; Min, Lingjiang; Zhu, Zhendong (Frontiers in Cell and Developmental Biology, 2025)
Mitochondrial dysfunction causes an increase in oxidative stress and depletion in ATP production. Studies have shown that mitochonic acid 5 (MA-5) improves cellular mitochondrial metabolism and ATP production. To this end, varying concentrations of MA-5 (0.01, 0.1, 1, and 10 nM) were added to a BTS extender, and thereafter, sperm motility and morphological parameters were assessed. Results indicate that adding 1 nM MA-5 significantly enhanced boar sperm motility and progressive motility, with higher values observed at the 1- and 2-h time points compared to the control. Sperm membrane and acrosome integrity values between the control and treatment groups were not different, except for 10 nM MA-5, which caused a reduction in membrane integrity. Treatment with MA-5, specifically 1 nM MA-5, also significantly boosted mitochondrial membrane potential and ATP content at the 2-h incubation point. In addition, MA-5 treatments stabilized mitochondrial transcription and translation processes, maintained overall sperm functionality, increased NADPH dehydrogenase subunits 1 (MT-ND1) and NADPH dehydrogenase subunits 6 (MT-ND6) protein and gene expression, and affected mitochondrial transcription factor A (TFAM) levels. However, after 4 h of incubation with MA-5, a decline in sperm quality parameters and an increase in ROS levels were observed. Interestingly, adding 10 nM pyrroloquinoline quinone (PQQ) and MA-5 to the extender restored mitochondrial function by enhancing mitochondrial potential and ATP content after 4 h of incubation. Overall, treatment with 1 nM MA-5 can help maintain sperm quality and mitochondrial metabolism during incubation (up to 2 h) at 37oC. Moreover, addition of a combination of MA-5 and 10 nM PQQ to the boar sperm extender is crucial for maintaining high-quality reproduction after 4 h of incubation. Consequently, MA-5 and PQQ play a role in maintaining sperm quality and mitochondrial function and can help in boar sperm preservation and artificial insemination (AI) practices.